Analysis of Working Capital with reference to Dr Reddy’s Laboratory - Sarika Gupta (JOURNAL OF MANAGEMENT, SCIENCES, OPERATION & STRATEGIES, 2023)
Working capital is a vital activity of the financial management. Managing working capital refers allocating assets in optimum manner to meet current and short term obligation of the business firm in efficient manner to realized their potential and minimize misappropriation working capital.